Implementation of the State of Law Principles from the Constitutional Law Perspective: A Case Study of Legislative Aspects in Law Enforcement in Indonesia - Pakpahan, Zainal Abidin; Yasmin, Ananda Sabillah; Safitri, Indri Tiya; Nainggolan, Elian S Christoper; Nasution, Thorique Akbar Maulana (Mahadi: Indonesia Journal of Law, 2024)
The Fourth Amendment to the 1945 Constitution of the Republic of Indonesia, enacted in 2002, officially established the concept of the State of Law, or "Rechtsstaat," which was previously only mentioned in the Explanation of the 1945 Constitution. This concept was solidified in Article 1, paragraph (3), which states, "The State of Indonesia is a State of law." This study utilizes a normative legal research method, focusing on document analysis using various secondary data sources such as legal literature, court decisions, legal doctrines, and expert opinions. The research's analysis centers on the implementation of the rule of law principles within the constitutional framework, with a specific focus on legislation and law enforcement in Indonesia, particularly in the legislative domain. Despite efforts to reform legislation, there are still deficiencies in the legislative process that may hinder the effective implementation of the rule of law principles. Some challenges include inconsistencies in laws, the intricate nature of the legislative process, and potential political interventions that could compromise the independence of legislative bodies.